2013
DOI: 10.4103/0259-1162.113987
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dexmedetomidine as an additive to local anesthetics in peribulbar block for cataract surgery

Abstract: Background and Objectives:We evaluated the effect of adding dexmedetomidine to lidocaine and bupivacaine for peribulbar block in two different doses. The primary endpoints were the onset and duration of corneal anesthesia, globe akinesia, and duration of analgesia.Materials and Methods:A randomized controlled clinical trial was conducted on 90 ASA I-II patients scheduled for elective cataract surgery under peribulbar anesthesia. Patients were randomly allocated to one of three groups of 30 each; group C (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 14 publications
10
31
1
Order By: Relevance
“…This study agrees with the results of Channabasappa et al [16], who examined two doses of dexmedetomidine as additive to admixture of lidocaine and bupivacaine in peribulbar anesthesia and they found that administration of dexmedetomidine accelerated the onset of the peribulbar anesthesia, prolonged its duration, and duration of postoperative analgesia. Moreover, they found that the dose of 50 μg dexmedetomidine produced sedation which made the patient more cooperative.…”
Section: Discussionsupporting
confidence: 82%
“…This study agrees with the results of Channabasappa et al [16], who examined two doses of dexmedetomidine as additive to admixture of lidocaine and bupivacaine in peribulbar anesthesia and they found that administration of dexmedetomidine accelerated the onset of the peribulbar anesthesia, prolonged its duration, and duration of postoperative analgesia. Moreover, they found that the dose of 50 μg dexmedetomidine produced sedation which made the patient more cooperative.…”
Section: Discussionsupporting
confidence: 82%
“…Our result was in line with the study carried by Channabasappa et al [10], who added dexmedetomidine to local anesthetics used for peribulbar anesthesia and reported that adding dexmedetomidine shortens the onset time and prolongs the duration of sensory and motor block, and produces sedation. Poonam Nehra et al [19] compared the addition of fentanyl vs. clonidine (alpha 2 agonist) to local anaesthetic mixture during peribulbar block and reported that the onset time of globe akinesia was significantly shorter in fentanyl group (F) and clonidine group (C) compared to control group (S).…”
Section: Discussionsupporting
confidence: 82%
“…This result is support by the study done by Channabasappa et al [10], who recorded that there was a significant increase in modified Ramsay score when he used dexmedetomidine in two doses (25 μg, 50 μg) added to local anesthetics used for peribulbar block.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Addition of dexmedetomidine to lidocaine and bupivacaine in peribulbar block shortens the onset time and prolongs the duration of the block and postoperative analgesia. It also provides sedation which enables full cooperation and potentially better operating conditions [9] . In addition to this, it also decreases the intraocular pressure significantly [10] .…”
Section: Peribulbar Anaesthesiamentioning
confidence: 99%